The effect of slip velocity on unsteady peristalsis MHD blood flow through a constricted artery experiencing body acceleration - Nandal, Jagdish; Kumari, Suchetha; Rathee, Rajbala (Zielona Góra: Uniwersytet Zielonogórski)
In this analysis, we present a theoretical study to examine the combined effect of both slip velocity and periodic body acceleration on an unsteady generalized non-Newtonian blood flow through a stenosed artery with permeable wall. A constant transverse magnetic field is applied on the peristaltic flow of blood, treating it as an elastico-viscous, electrically conducting and incompressible fluid.
Keywords: elastico-viscous; slip velocity; selective permeability; peristalsis; stenosed artery